2020
DOI: 10.1038/s41598-020-74350-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of small molecule FPR1 antagonists in the treatment of cancers

Abstract: The formylpeptide receptor-1 (FPR1) is a member of the chemotactic GPCR-7TM formyl peptide receptor family, whose principle function is in trafficking of various leukocytes into sites of bacterial infection and inflammation. More recently, FPR1 has been shown to be expressed in different types of cancer and in this context, plays a significant role in their expansion, resistance and recurrence. ICT12035 is a selective and potent (30 nM in calcium mobilisation assay) small molecule FPR1 antagonist. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…These genes were mainly enriched in small molecule metabolic processes, cellular protein metabolic processes and cellular lipid metabolic processes. Studies of human primary and metastatic tumour tissue samples have shown that the metabolism of many small molecules is associated with the metastasis of tumours 41 43 . For example, the expression of the small-molecule inhibitor CKB is enhanced in liver metastases and inhibits extracellular small molecule metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These genes were mainly enriched in small molecule metabolic processes, cellular protein metabolic processes and cellular lipid metabolic processes. Studies of human primary and metastatic tumour tissue samples have shown that the metabolism of many small molecules is associated with the metastasis of tumours 41 43 . For example, the expression of the small-molecule inhibitor CKB is enhanced in liver metastases and inhibits extracellular small molecule metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of FPR1 in healthy, non-immune cells is low, a number of tumors have been shown to express significant levels of FPR1 (25)(26)(27)(28)(29)(30). Importantly, a previous study indicated that targeting FPR1 by ICT12035, a selective small molecule antagonist, can provide a new avenue for the therapy of cancers (31). Therefore, further investigation of FPR1 antagonists can provide opportunities for more efficient treatment of cancers, including bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a variety of synthetic molecules have been identified that antagonize and/or inhibit FPR1‐mediated responses. Among the large number of different FPR1 inhibitors, the most potent and selective compounds described so far, belong to a group of novel pyrazoles 85–87 . These FPR1 antagonists are not commercially available but they might be important tool compounds for future studies of the role of this receptor in initiation as well as the resolution of inflammatory reactions.…”
Section: Defined Neutrophil Gpcrsmentioning
confidence: 99%